2021
DOI: 10.1002/jmv.26834
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary analysis of SARS‐CoV‐2 spike protein for its different clades

Abstract: The spike protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become the main target for antiviral and vaccine development. Despite its relevance, e information is scarse about its evolutionary traces. The aim of this study was to investigate the diversification patterns of the spike for each clade of SARS-CoV-2 through different approaches. Two thousand and one hundred sequences representing the seven clades of the SARS-CoV-2 were included. Patterns of genetic diversifications and nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Recent studies have investigated the evolution and spatiotemporal distribution of SARS-CoV-2 via haplotype networks. Pereson, MJ, et al studied the diversification of the spike protein in each SARS-CoV-2 clade, showing that two haplotypes predominated in specific clades (Hap-1 for clades G, GH and GR; and Hap-2 for clades L, O, S and V) [46]. In addition, sequence similarity and network structure were used to infer the import of SARS-CoV-2 from multiple countries in Bangladesh [47].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have investigated the evolution and spatiotemporal distribution of SARS-CoV-2 via haplotype networks. Pereson, MJ, et al studied the diversification of the spike protein in each SARS-CoV-2 clade, showing that two haplotypes predominated in specific clades (Hap-1 for clades G, GH and GR; and Hap-2 for clades L, O, S and V) [46]. In addition, sequence similarity and network structure were used to infer the import of SARS-CoV-2 from multiple countries in Bangladesh [47].…”
Section: Discussionmentioning
confidence: 99%
“…A first study reported the nucleotide MR of Spike gene from January to April 2020 at 2.19 × 10 −3 substitution/site/year, 47 which was significantly higher than the MR of the entire genome 48,49 . At 9th month, the MR remained unvaried at 1.08 × 10 −3 ribonucleotide substitutions/site/year, without differences among clades 50 . The global frequencies of different immune escape variants has been assessed in several research articles 51 .…”
Section: Spike Protein Mutations Detected In Currently Circulating Strainsmentioning
confidence: 99%
“…Since evolutionary rate does not vary much, this also signifies the low percentage variance observed in our study. 28 We observed that the position of the genes along the horizontal axis (Figure 1 ) were significantly correlated with the hydrophobicity of the encoded proteins ( r = .45, p < .01).The average value of the hydrophobicity of the spike proteins distributed in the negative side of the horizontal axis is −0.0767 ( SD : 0.00174) and the average value of the hydrophobicity of the spike proteins distributed in the negative side of the horizontal axis is −0.0750 ( SD : 0.00191).We have also observed that average hydrophobicity of the spike proteins distributed in the negative side of the horizontal axis is significantly lower ( p < .0001) than the average hydrophobicity of the spike proteins distributed in the positive side of the horizontal axis. For lucidity, henceforth, spike proteins distributed in the positive side of the horizontal axis will be referred to as SPMHR and spike proteins distributed in the negative side of the horizontal axis will be referred to as SPLHR.…”
Section: Resultsmentioning
confidence: 99%